Diversity and Weed Dominance in Coconut Plantation Area At diferent Crop Stadiums in Tial Village, Central Maluku District - Tanasale, Vilma Laurien; Kilkoda, Abdul Karim; Lahalimu, Zulkarnaen (CROPSAVER, 2024)
Weeds are plants whose presence is unwanted because they interfere with and reduce the yield of cultivated plants. One of the plantation crops with high economic value is coconut. Coconut is a commodity that can make a major contribution to the economy in Indonesia. The presence of weeds in coconut plantations will reduce yields. This study aims to determine the diversity and dominance of weed species that grow in the coconut plantation area in Tial Village, Central Maluku Regency. This study uses the "weed survey" method to collect data by direct observation in the field. In conducting vegetation analysis, the quadratic method was used with a sample plot measuring 1 m x 1 m. For sampling in the coconut planting area in Tial Country, 6 plant samples were taken at each plant stage to obtain 12 plant samples and repeated 3 times to obtain 36 observation samples. Observations of weeds in Tial Village showed that in the immature coconut planting area, there were 11 broadleaf weed species from 10 broadleaf weed families, 3 pakisan weed species from 2 pakisan weed families and 1 grassy weed species from the Poaceae and 1 type of tekian weed from the Cypeaceae tribe, as well as from observations of weeds in Tial Village, it shows that in the coconut plantation area at the productive stage, there are 13 types of broadleaf weeds from 11 broadleaf weed families, 2 types of pakisan weeds from 1 pakisan weed tribe and 1 type of grass weed from the Poaceae tribe and 1 type of tekian weed from the Cypeaceae tribe. Based on the total dominant value Summed Domination Ratio (SDR) the immature plant had the highest value, Thuja occidentalis 26.78 percent from the Convovulaceae tribe. In the coconut planting area the mature stage of the plant having the highest SDR value was Stelaria holasta.L 29.21 percent from the Caryophylaceae.